War and Politics by Other Means : A Journalist's Memoir - Scates, Shelby (Book collections on Project MUSE., 2000)
"As a newsman he reported on those American climbers who triumphed, though not without suffering great personal losses, by reaching the top of K2 in 1978. Scates used his considerable journalistic experience and inventiveness to get the story of this epic climb quickly back to the United States. He also describes his own midlife climb of Mt. McKinley with two friends."--Jacket